Pemertahanan dan Pergeseran Bahasa pada Anak dari Keluarga Multietnis (Studi Kasus Pada Mahasiswa Jurusan Bahasa dan Sastra Inggris Fakultas Adab UIN STS Jambi) - Ulfatmi Azlan (Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2019)
This research discusses language maintenance and language shift among children from intermarriage family. It could be found in a society that many children who grow up from intermarriage family have bilingual and multilingual. But in some cases, this condition also become the factors that cause them losing their cultural identity due to their parents do not introduce and teach them their mother tongue language. This condition will be affected the existence of those local languages because it could make them appear or even the worst thing that it could make them become death. Those effects have been found in many local languages in Indonesia in which many local languages have extinct and some of them are going to be extinct. The aims of this research are to describe the phenomenon that appears within the students of English Language and Literature Adab and Humanities Faculty UIN STS Jambi who have intermarriages family’s background. Besides that, it also aims to find out the role of parents to decide the language choice used by their children. Since this research lay down from the previous researchers that find out parents are the important role in deciding language choice for their children. Observation and questionnaire are the techniques used in collecting the data. The results show that parents have a role that causes the shift and the maintenance of local languages. In addition, the factors such as bilingual, language’s choosing and using at home and migration are the causes of language shift found in English Language and Literature students. But the researcher found that code switching and code mixing are only used by the students for a specific situation where they should elaborate their language with their listeners.